The Effect of LMX and Competence on Employee Performance with Motivation as a Mediating Variable - Aldila Nisa Ilmatu Tsaabita; Tristiana Rijanti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to see how LMX and Competency affect Performance with Motivation as a mediating variable in the Regional Secretariat of Temanggung Regency. The population is the total number of civil servants in the Temanggung Regency Regional Secretariat of 101 employees. The study used non-probability sampling using a saturated sampling technique where the sample number was 101 employees. Data was collected using questionnaires and then analyzed using multiple regression analysis techniques to see how the variables were related. The results showed that LMX had a positive and significant effect on motivation, competence had a positive and significant effect on motivation, competence had a positive and significant effect on performance, motivation had a positive and significant effect on performance, motivation mediated the influence of LMX on performance, and motivation mediated the effect of competence on performance. LMX has no effect on performance.